A proof of the inverse function theorem (1971)
The purpose of this note is to give a proof, hopefully new, of the inverse function theorem as an application of the local existence theorem for differential equations. If Ω  is an open subset of a Banach space E and T: Ω → E is of class C1, then T is locally bounded and satisfies a Lipschitz condition at every point.